Complementation analysis of fatty acid oxidation disorders. - A Moon; W J Rhead (The Journal of Clinical Investigation, 1987)
We assayed [9,10(n)-3H]palmitate oxidation by fibroblast monolayers from patients with fatty acid oxidation disorders. Activities in the different disorders were (percent control): short-chain acyl-coenzyme A (CoA) dehydrogenase deficiency (115%), medium chain acyl-CoA dehydrogenase deficiency (18%), long-chain acyl-CoA dehydrogenase deficiency (28%), multiple acyl-CoA dehydrogenation disorder, mild and severe variants (49% and 7%), and palmityl-carnitine transferase deficiency (4%). Multiple acyl-CoA dehydrogenation disorder, medium chain acyl-CoA dehydrogenase-deficient lines, and long-chain acyl-CoA dehydrogenase-deficient lines all complemented one another after polyethylene glycol fusion, with average activity increases of 31-83%. We detected two complementation groups in the severe multiple acyl-CoA dehydrogenation disorder lines, consistent with deficiencies of either electron transfer flavoprotein or electron transfer flavoprotein:ubiquinone oxidoreductase. The metabolic block in the latter cell lines is threefold more severe than in the former (P less than 0.001). No intragenic complementation was observed within either group. We assigned two patients with previously unreported severe multiple acyl-CoA dehydrogenation disorder to the electron transfer flavoprotein:ubiquinone oxido-reductase-deficient group.